The Importance of Information Science in the definition of Public Policies - Kettner Filho, Renato; D. J. de Macedo, Douglas (Advanced Notes in Information Science, 2023)
The present work aims, through bibliographical research and literature review, to bring the main definitions of Information Science, Public Policies, Information Society, and Information Policies, as well as to identify the importance that, nowadays Information Science has in the definition and monitoring of Government Public Policies, standing out as an essential control tool and identification of needs and deficiencies to be provided by the State and for the strengthening of citizenship. An example of a government tool that can contribute to creating and supervising state Public Policies (Transparency Portal) is also exposed. The importance of bringing together the branches of Information Science and Public Policy for developing, evaluating, and inspecting procedures related to social measures adopted by state bodies was verified. Thus, the relevance of using Information Science principles was also identified to enable increasingly greater and easier participation of individuals directly interested in the elaboration and supervision of Public Policies: the citizens.